ETHANOL EXTRACT LIQUID SOAP FORMULATION LEAVES OF CELERY (Apium graveolens L.) AGAINST Escherichia coli BACTERIA - Irwanto, Reno; Apriani Girsang, Santa Dewi; Maria Ginting, Wira; Novia, Reni (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Dirty hands will be a source of disease. Soap is a pharmaceutical preparation used to maintain health. Celery (Apium graveolens L.) is a plant of the Apiaceae tribe with a distinctive menthol aroma. This study aimed to determine the inhibitory power of celery leaf extract formulation (Apium graveolens L.) as an antibacterial hand-washing soap. This research method is a type of experimental research. The stages of the research were collecting samples, identifying plants, making simplicia, characterizing simplicia, screening phytochemicals, making extracts and making hand soap formulations of celery leaf extract (Apium graveolens L) at concentrations of 5%, 10%, 15% and antibacterial testing of celery leaves, against Escherichia coli bacteria. The results showed the celery leaf extract soap formulation contained phytochemical compounds of flavonoids, tannins and saponins. The organoleptic test found that the best soap formulation was the F2 formulation with a concentration of 10% at an average level of preference value, namely 3.67 for colour, 3.27 for aroma, and 3.80 for texture. The homogeneity test performed showed that all formulations produced soap with good homogeneity. The height and stability test of the resulting celery extract soap foam ranged from 61-71 mm. The irritation test of the resulting celery extract soap also showed no irritation for all the formulations. The value of the antibacterial activity test found that the F1 formulation showed antibacterial activity with an inhibition zone diameter of 3 (weak), F2 with an inhibition zone of 9 (moderate) and F3 with the antibacterial activity of 12 (strong).